Food science and technology (Wiley-Blackwell, 2009)
The study of food science and technology is the understanding and application of science to satisfy the needs of society for sustainable food quality, safety and security. Supported by IUFoST, this brand new comprehensive textbook is an invaluable tool, designed to cover all elements of the contemporary food science and technology course. Chapters in the book are drawn from an international team of authors comprising industry experts, teachers and researchers, with a view to ensuring applicability to the increasingly international way that the subject is taught. Carefully peer reviewed and edited, the book is an essential piece of equipment for all students and teachers, and also serves as a reference for qualified professionals already working in the food industry worldwide.